Multi-omics Approaches to CCAAT/Enhancer-Binding Protein Beta in Oral Squamous Cell Carcinoma: Crosstalk Between Tumor Cells andTumor-Associated Macrophages Driving Disease Progression - Li, Min; Liu, Jilun; Zhang, Wenjuan; Sun, Ruonan; Wang, Wenjing; Liu, Xin; Jin, Linyu; Qiu, Yongle (Current Cancer Drug Targets, 2025)
<span class=
Keywords: enhancer